Numerical Representations and User Behaviour in Social Networking Sites: Towards a Multi- Theoretical Research Framework - Sjöklint, Mimmi; Constantiou, Ioanna; Trier, Matthias (ECIS 2013 Proceedings)
The new technological enhancements and the accessibility to varieties of online applications, enable users to collect personal data and perform self-evaluation through test, comparison and experimentation. The sparked interest in numbers and numbers as self-representative visualisations is prominent in social networking sites, which are the empirical setting for the present study. This paper sets out to establish a multi-theoretical framework which enables the investigation of emerging phenomena of the role of numbers in social networking sites. The proposed framework rests on three theoretical pillars: self-determination theory, heuristic decision making and behavioural economics. A discussion departs from these convictions to investigate user reactions and behaviour when faced with numerical representations in the SNS.
Keywords: User Behaviour; Social Networking Sites; Numerical Representations; Multi-Theoretical Framework; Quantified Self; Pointification

"I Can Simply…"? Theorizing Simplicity as a Design Principle and Usage Factor - Trier, Matthias; Richter, Alexander
The usage of social software to support collaboration and knowledge management in corporate intranets is a pervasive topic in practice and research. However, there remain many open research questions concerning its socio-technical system design. To address this gap and to contribute to a deeper understanding of the role and success of corporate social software, we first identify and conceptualize simplicity as an influential design principle and usage factor. We propose a theoretical framework that helps us to empirically study the role of simplicity based on six case vignettes of corporate social software implementation and use. From the theoretical basis and the empirical analysis we develop a series of theoretical propositions and discuss implications for IS design and adoption.

Förderung medienpädagogischer Kompetenz angehender Lehrerinnen und Lehrer in der ersten Phase der Lehrerbildung - Klar, Tilman-Mathies

Countering Wrapping Attack on XML Signature in SOAP Message for Cloud Computing - Razzaghi Kouchaksaraei, Hadi; Chefranov, Alexander G. (International Journal of Computer Science and Information Security)
It is known that the exchange of information between web applications is done by means of the SOAP protocol. Securing this protocol is obviously a vital issue for any computer network. However, when it comes to cloud computing systems, the sensitivity of this issue rises, as the clients of system, release their data to the cloud. XML signature is employed to secure SOAP messages. However, there are also some weak points that have been identified, named as XML signature wrapping attacks, which have been categorized into four major groups; Simple Ancestry Context Attack, Optional element context attacks, Sibling Value Context Attack, Sibling Order Context. In this paper, two existing methods, for referencing the signed part of SOAP Message, named as ID referencing and XPath method, are analyzed and examined. In addition, a new method is proposed and tested, to secure the SOAP message. In the new method, the XML any signature wrapping attack is prevented by employing the concept of XML digital signature on the SOAP message. The results of conducted experiments show that the proposed method is approximately three times faster than the XPath method and even a little faster than ID.

Geometrical and optical benchmarking of copper guanidine-quinoline complexes: Insights from TD-DFT and many-body perturbation theory† - Jesser, Anton; Rohrmüller, Martin; Schmidt, Wolf Gero; Herres-Pawlis, Sonja (Journal of Computational Chemistry)

Friggeet al.Reply: - Frigge, T.; Wall, S.; Krenzer, B.; Wippermann, St.; Sanna, S.; Klasing, F.; Hanisch-Blicharski, A.; Kammler, M.; Schmidt, Wolf Gero; Horn-von Hoegen, M. (Physical Review Letters)

LiNb1-xTaxO3Electronic Structure and Optical Response fromFirst-PrinciplesCalculations - Riefer, A.; Sanna, S.; Schmidt, Wolf Gero (Ferroelectrics)

Charge compensation by long-period reconstruction in strongly polar lithium niobate surfaces - Sanna, S.; Rode, S.; Hölscher, R.; Klassen, S.; Marutschke, C.; Kobayashi, K.; Yamada, H.; Schmidt, Wolf Gero; Kühnle, A. (Physical Review B)

Adsorption of PTCDA on NaCl(100) and KCl(100) - Aldahhak, Hazem; Schmidt, Wolf Gero; Rauls, E. (Surface Science)

Monolayer Doping via Phosphonic Acid Grafting on Silicon: Microscopic Insight from Infrared Spectroscopy and Density Functional Theory Calculations - Longo, Roberto C.; Cho, Kyeongjae; Schmidt, Wolf Gero; Chabal, Yves J.; Thissen, Peter (Advanced Functional Materials)

Optical response of stoichiometric and congruent lithium niobate from first-principles calculations - Riefer, Arthur; Sanna, Simone; Schindlmayr, Arno; Schmidt, Wolf Gero (Physical Review B)
The frequency-dependent dielectric function and the second-order polarizability tensor of ferroelectric LiNbO3 are calculated from first principles. The calculations are based on the electronic structure obtained from density-functional theory. The subsequent application of the GW approximation to account for quasiparticle effects and the solution of the Bethe-Salpeter equation for the stoichiometric material yield a dielectric function that slightly overestimates the absorption onset and the oscillator strength in comparison with experimental measurements. Calculations at the level of the independent-particle approximation indicate that these deficiencies are, at least, partially related to the neglect of intrinsic defects typical for the congruent material. The second-order polarizability calculated within the independent-particle approximation predicts strong nonlinear coefficients for photon energies above 1.5 eV. The comparison with measured data suggests that the inclusion of self-energy effects in the nonlinear optical response leads to a better agreement with experiments. The intrinsic defects of congruent samples reduce the optical nonlinearities, in particular, for the 21 and 31 tensor components, further improving the agreement between experiments and theory.

Structural variety of 5-fluoroarene-2-aminopyrimidine in comparison to 2-aminopyrimidine silver(i) coordination polymers: progress report and overview - Eberhard, Jens; Stoll, Ion; Brockhinke, Regina; Neumann, Beate; Stammler, Hans-Georg; Riefer, Arthur; Rauls, Eva; Schmidt, Wolf Gero; Mattay, Jochen (CrystEngComm)

Bis-μ-oxo and μ-η2:η2-peroxo dicopper complexes studied within (time-dependent) density-functional and many-body perturbation theory - Rohrmüller, M.; Herres-Pawlis, S.; Witte, M.; Schmidt, Wolf Gero (Journal of Computational Chemistry)

Atomic Structure of Interface States in Silicon Heterojunction Solar Cells - George, B. M.; Behrends, J.; Schnegg, A.; Schulze, T. F.; Fehr, M.; Korte, L.; Rech, B.; Lips, K.; Rohrmüller, M.; Rauls, E.; Schmidt, Wolf Gero; Gerstmann, U. (Physical Review Letters)

On Semeai Detection in Monte-Carlo Go. - Graf, Tobias; Schäfers, Lars; Platzner, Marco (Proceedings of the International Conference on Computers and Games (CG))

LiNb1-xTaxO3Electronic Structure and Optical Response fromFirst-PrinciplesCalculations - Riefer, A.; Sanna, S.; Schmidt, Wolf Gero (Ferroelectrics)

A fully integrated 120-GHz six-port receiver front-end in a 130-nm SiGe BiCMOS technology - Laemmle, Benjamin; Schmalz, Klaus; Borngräber, Johannes; Scheytt, Christoph; Weigel, Robert; Koelpin, Alexander; Kissinger, Dietmar (Silicon Monolithic Integrated Circuits in RF Systems (SiRF), 2013 IEEE 13th Topical Meeting on)
A fully integrated six-port receiver front-end at 120 GHz center frequency including a low-noise-amplifier, a passive six-port network, a VCO, and four direct converters is presented in this publication. The overall architecture of the designed six-port receiver is analyzed and fundamental theory of the receiver given. The design of the six-port building blocks is described and measurement results are presented. All circuits have been fabricated in a 0.13μm 300-GHz f T SiGe BiCMOS technology. The fully integrated receiver consumes 85.9 rnA from a 3.3-V supply and occupies an area of 1.03mm 2 . The receiver includes a VCO with a center frequency of 117.15 GHz, a tuning range of 2.7 GHz, and a phase noise of -86 dBc/Hz at 1 MHz offset. The LNA shows a gain of 12 dB, a 3-dB bandwidth of 30 GHz at a power consumption of 9.2 rnA. The six-port core has a conversion gain of 3.6 dB, a P 1dB of -12 dBm, and a power consumption of 28 rnA. The overall receiver shows a conversion gain of 2.4 dB at 120 GHz and P 1dB of -17 dBm.

Integrator and digitizer for a non-coherent IR-UWB receiver - Digel, Johannes; Masini, Michelangelo; Grözing, Markus; Berroth, Manfred; Fischer, Gunter; Olonbayar, Sonom; Gustat, Hans; Scheytt, Christoph (Silicon Monolithic Integrated Circuits in RF Systems (SiRF), 2013 IEEE 13th Topical Meeting on)
Impulse-radio ultra-wideband systems (IR-UWB) provide short-range wireless communication and precise localization simultaneously. Especially non-coherent IR-UWB reduces the system complexity which enables the design of low-power receivers. This paper presents an integrating digitizer which integrates rectified baseband pulses of an IR-UWB signal and provides the digitized data to the digital baseband of the receiver. The integrator is composed of two time-interleaved (TI) operational amplifiers with capacitive feedback. With this structure, the integrator can be periodically reset without introducing a dead time between two integration periods. The analog-to-digital conversion is performed by a 6 bit 62.4 MS/s successive approximation register analog-to-digital converter (SAR ADC). The integrating digitizer chip is realized in a 250 nm SiGe:C BiCMOS technology from IHP.

A low-cost miniature 120GHz SiP FMCW/CW radar sensor with software linearization - Sun, Yaoming; Marinkovic, Miroslav; Fischer, Gunter; Winkler, Wolfgang; Debski, Wojciech; Beer, Stefan; Zwick, Thomas; Girma, Mekdes Gebresilassie; Hasch, Jürgen; Scheytt, Christoph (Solid-State Circuits Conference Digest of Technical Papers (ISSCC), 2013 IEEE International)
This paper presents an integrated mixed-signal 120GHz FMCW/CW radar chipset in a 0.13μm SiGe BiCMOS technology. It features on-chip MMW built-in-self-test (BIST) circuits, a harmonic transceiver, software linearization (SWL) circuits and a digital interface. This chipset has been tested in a low-cost package, where the antennas are integrated. Above 100GHz, our transceiver has achieved state-ofthe-art integration level and receiver linearity, and DC power consumption.

Towards mm-wave System-On-Chip with integrated antennas for low-cost 122 and 245 GHz radar sensors - Scheytt, Christoph; Sun, Yaoming; Schmalz, Klaus; Mao, Yanfei; Wang, Ruoyu; Debski, Wojciech; Winkler, Wolfgang (Silicon Monolithic Integrated Circuits in RF Systems (SiRF), 2013 IEEE 13th Topical Meeting on)
Complex integrated 122 and 245 GHz SiGe BiCMOS transceiver ICs as well as an efficient broadband on-chip antenna are presented. The ICs target radar and sensing applications for the ISM bands at 122 and 245 GHz. Due to high level of integration and basic mm-wave self-testing production as well as test cost are dramatically reduced. Furthermore a compact and efficient on-chip antenna allows for chip-on-board mounting without RF interfaces.

49 GHz 6-bit programmable divider in SiGe BiCMOS - Ergintav, Arzu; Sun, Yaoming; Scheytt, Christoph; Gürbüz, Yasar (Silicon Monolithic Integrated Circuits in RF Systems (SiRF), 2013 IEEE 13th Topical Meeting on)
In this paper, a 6-bit true modular programmable frequency divider with division ratios ranging from 64 to 127 is reported. It is composed of a divider chain of 6 divide-by-2/3 cells, and ECL stages that are introduced as synchronization circuits for programming inputs. The synchronization circuits have CMOS input for compatibility with programming circuits. The stand-alone divider chain is functional up to an input clock frequency of 49 GHz. The combination of the divider chain with synchronization circuits is functional up to 44 GHz. The 6 stage divider draws 34 mA current from a 2.7 V supply. The synchronization circuits draw 30 mA from a 3 V supply. The circuit is fabricated in a 0.13 μm SiGe BiCMOS technology, and is well suited for millimeter-wave phase-locked loop (PLL) circuits which require fine frequency resolution.

245 GHz subharmonic receivers in SiGe - Mao, Yanfei; Schmalz, Klaus; Borngräber, Johannes; Scheytt, Christoph (2013 IEEE Radio Frequency Integrated Circuits (RFIC) Symposium)
Two subharmonic receivers for 245 GHz spectroscopy sensor applications in the 245 GHz ISM band have been proposed. One receiver consists of an 2nd APDP (antiparallel diode pair) passive SHM (subharmonic mixer), a 120 GHz push-push VCO with 1/64 divider, and a 120 GHz PA (power amplifier). The other consists of a single-ended four-stage CB (common base) LNA, an 2 nd APDP passive SHM, an IF amplifier, a 120 GHz push-push VCO with 1/64 divider, and a 120 GHz PA. The receivers are fabricated in a SiGe:C BiCMOS technology with f T /f max =300/500 GHz. The measured conversion gain are -17 dB rsp. 10.6 dB at 245 GHz with 3-dB bandwidths of 13 GHz rsp. 14 GHz, and the single-side band noise figure are 17 dB rsp. 20 dB; the two receivers dissipates a power of 213 mW and 312 mW, respectively.

A 240 GHz Direct Conversion IQ Receiver in 0.13 µm SiGe BiCMOS technology - Elkhouly, Mohamed; Mao, Yanfei; Meliani, Chafik; Ellinger, Frank; Scheytt, Christoph (2013 IEEE Radio Frequency Integrated Circuits (RFIC) Symposium,)
A 240 GHz direct conversion IQ receiver manufactured in 0.13 SiGe BiCMOS technology with f T /f max of 300/500 GHz is presented. The receiver consists of a four stage LNA, an active power divider, an LO IQ generation network, and direct down-conversion fundamental mixers. The integrated IQ receiver yields a conversion gain of 18 dB, an 18 dB simulated DSB NF, and a 3 dB bandwidth of 25 GHz. The required 245 GHz LO power is in the order of -10 dBm. The receiver exhibits an IQ amplitude and phase imbalance of 1 dB and 3° respectively. It draws 135 mA from the 3.5 V supply and 20 mA from 2 V.

245 GHz Subharmonic Receiver in SiGe - Mao, Yanfei; Schmalz, Klaus; Borngräber, Johannes; Scheytt, Christoph; Meliani, Chafik (IEEE International Microwave Symposium, Advances in Low Noise Amplifiers and Receivers)
A subharmonic receiver for 245 GHz spectroscopy sensor applications have been proposed. The receiver consists of a CB (common base) LNA, 2 nd transconductance SHM (subharmonic mixer) and a 120 GHz push-push VCO with 1/64 divider. The receiver is fabricated in f T /f max =300/500 GHz SiGe: C BiCMOS technology. Its measured single-ended gain is 14.3 dB at 245 GHz with tuning range of 15 GHz, and the single-side band noise figure is 19 dB. The input 1-dB compression point is at -24 dBm. The receiver dissipates a power of 200 mW.

Wireless 100Gb/s Using A Powerand - Scheytt, Christoph (IEEE International Conference on Communications)

Hardware-Effizientes Mixed-Signal Entzerrfilter - Scheytt, Christoph

Konzipierung eines selbstoptimierenden hybriden Energiespeichersystems unter besonderer Berücksichtigung der Verlässlichkeit - Gausemeier, Jürgen; Iwanek, Peter; Dorociak, Rafal; Stille, Karl Stephan Christian; Böcker, Joachim (Wissenschaftsforum Intelligente Technische Systeme, 9. Paderborner Workshop Entwurf mechatronischer Systeme)
Die absehbare Entwicklung der Informations- und Kommunikationstechnik wird mechatronische Systeme mit inhärenter Teilintelligenz ermöglichen. Hierfür verwenden wir den Begriff Selbstoptimierung (S.O.). Selbstoptimierende (s.o.) Systeme reagieren autonom und flexibel auf sich ändernde Umfeldbedingungen [ADG+09]. Die Entwicklung derartiger Systeme erfordert eine enge Zusammenarbeit der Entwickler der beteiligten Domänen Mechanik, Elektrik/Elektronik, Regelungstechnik und Softwaretechnik. In diesem Beitrag wird erklärt, wie die Steigerung der Verlässlichkeit durch S.O. bei der Konzipierung eines s.o. Systems adäquat berücksichtigt wird. Die Konzipierung des hybriden Energiespeichersystems des innovativen Schienenfahrzeugs RailCab wird retrospektive durchgeführt. Dies erfolgt von der ersten Funktionsdefinition über die Lösungsauswahl und die dazugehörige Nutzwertanalyse bis hin zur Produktkonzeption des Energiespeichersystems. Es wird gezeigt, wie die Schwachstellen und Widersprüche eines technischen Systems identifiziert sowie mit Hilfe geeigneter Gegenmaßnahmen behoben werden können. Hierbei soll insbesondere die Integration der S.O. als Möglichkeit zur Behebung der Schwachstellen betrachtet werden. Somit wird gezeigt wann und wie die Entscheidung über die s.o. Auslegung des Systems getroffen und die Steigerung der Verlässlichkeit dabei ins Kalkül gezogen wird.
Keywords: Konzipierung; Selbstoptimierung; Verlässlichkeit; Mechatronik; Hybrider Energiespeicher; LEA-Publikation; Eigene

Selbstoptimierung in der Anwendung - Böcker, Joachim; Buchholz, Oleg; Romaus, Christoph; Schulte, Christoph; Stille, Karl Stephan Christian (Wissenschaftsforum Intelligente Technische Systeme, 9. Paderborner Workshop Entwurf mechatronischer Systeme)
Die absehbare Entwicklung der Informations- und Kommunikationstechnik wird mechatronische Systeme mit inhärenter Teilintelligenz ermöglichen. Hierfür verwenden wir den Begriff Selbstoptimierung (S.O.). Selbstoptimierende (s.o.) Systeme reagieren autonom und flexibel auf sich ändernde Umfeldbedingungen [ADG+09]. Die Entwicklung derartiger Systeme erfordert eine enge Zusammenarbeit der Entwickler der beteiligten Domänen Mechanik, Elektrik/Elektronik, Regelungstechnik und Softwaretechnik. In diesem Beitrag wird erklärt, wie die Steigerung der Verlässlichkeit durch S.O. bei der Konzipierung eines s.o. Systems adäquat berücksichtigt wird. Die Konzipierung des hybriden Energiespeichersystems des innovativen Schienenfahrzeugs RailCab wird retrospektive durchgeführt. Dies erfolgt von der ersten Funktionsdefinition über die Lösungsauswahl und die dazugehörige Nutzwertanalyse bis hin zur Produktkonzeption des Energiespeichersystems. Es wird gezeigt, wie die Schwachstellen und Widersprüche eines technischen Systems identifiziert sowie mit Hilfe geeigneter Gegenmaßnahmen behoben werden können. Hierbei soll insbesondere die Integration der S.O. als Möglichkeit zur Behebung der Schwachstellen betrachtet werden. Somit wird gezeigt wann und wie die Entscheidung über die s.o. Auslegung des Systems getroffen und die Steigerung der Verlässlichkeit dabei ins Kalkül gezogen wird.
Keywords: Konzipierung; Selbstoptimierung; Verlässlichkeit; Mechatronik; Hybrider Energiespeicher; LEA-Publikation; Eigene

Crosslinked Test Benches - Stille, Karl Stephan Christian; Böcker, Joachim (Design Methodology for Intelligent Technical Systems)
Keywords: Eigene

Online capable optimized planning of power split in a hybrid energy storage system - Stille, Karl Stephan Christian; Romaus, Christoph; Böcker, Joachim (Eurocon 2013)

Self-optimization energy management considering stochastic influences for a hybrid energy storage of an electric road vehicle - Romaus, Christoph; Wimmelbücker, Dominik; Stille, Karl Stephan Christian; Böcker, Joachim (2013 International Electric Machines & Drives Conference)

Contradictions and the Foundation of Logic in German Idealism - Ficara, Elena (La question de la logique dans l’Idéalisme allemande)

Kant e il rapporto dello scetticismo con la filosofia - Ficara, Elena (Akten des XI. Kant Kongresses)

Hegel Within Contemporary Logic - Ficara, Elena (Teoria)

Dialectic and Dialetheism - Ficara, Elena (History and Philosophy of Logic)

Wirkungsgradoptimale Arbeitspunktsteuerung für einen permanenterregten Synchronmotor mit vergrabenen Magneten unter Berücksichtigung von Temperatureinflüssen - Wallscheid, Oliver; Böcker, Joachim (ETG-Fachbericht-Internationaler ETG-Kongress 2013–Energieversorgung auf dem Weg nach 2050)

Discrete-time model of an IPMSM based on variational integrators - Specht, Andreas; Ober-Blöbaum, Sina; Wallscheid, Oliver; Romaus, Christoph; Böcker, Joachim (Electric Machines & Drives Conference (IEMDC), 2013 IEEE International)

The Berlin Group and the Philosophy of Logical Empiricism
Rezensionen: Zbl. Math. 1275.03016 (Leon Harkleroad)

Practice budgets and the patient mix of physicians-Evaluating the effects of remuneration system reforms on physician behaviour in Germany - Schmitz, Hendrik (Journal of Health Economics)

What accounts for the regional differences in the utilisation of hospitals in Germany? - Augurzky, Boris; Kopetsch, Thomas; Schmitz, Hendrik (The European Journal of Health Economics)

Health and the double burden of full-time work and informal care provision—Evidence from administrative data - Schmitz, Hendrik; Stroka, Magdalena A (Labour Economics)

Two-Phase Interleaving Configuration of the LLC Resonant Converter - Analysis and Experimental Evaluation - Figge, Heiko; Grote, Tobias; Fröhleke, Norbert; Böcker, Joachim; Schafmeister, Frank (Proc. IEEE Annual Industrial Electronics Society Conference (IECON))

Integrated Magnetic for DCM-PSFB Converter - Njiende, Hugues; Li, Rongyuan; Schafmeister, Frank; Ide, Peter

Resonant capacitor clamping circuit in resonant converter - Figge, Heiko; Schafmeister, Frank

Hybrid Energy Storage System (HES) - Stille, Karl Stephan Christian; Romaus, Christoph; Böcker, Joachim (Design Methodology for Intelligent Technical Systems)

Design of a high performance ferrite magnet-assisted synchronous reluctance motor for an electric vehicle - Paradkar, Milind; Böcker, Joachim (IECON 2012 - 38th Annual Conference on IEEE Industrial Electronics Society)

Fast online model predictive control of IPMSM using parallel computing on FPGA - Leuer, Michael; Böcker, Joachim (2013 International Electric Machines & Drives Conference)

Co-simulation of an electric traction drive - Schulte, Christoph; Böcker, Joachim (2013 International Electric Machines & Drives Conference)

Low Latency Hybrid Hardware-in-the-Loop Simulator for Railway Traction System - Tong, Laisheng; Zou, Huanqing; Sun, Meng; Böcker, Joachim (2013 IEEE Vehicle Power and Propulsion Conference (VPPC))

A Novel LC Resonant Based Partial Booster Scheme for Improved Efficiency and Reduced Cost of Transformerless Photovoltaic Inverters - Krishna, D.V.M.M.; Preckwinkel, H.; Fröhleke, N.; Böcker, Joachim (PCIM Europe Conference, Nürnberg, Germany)